PORTRAIT OF NATIONALISM VALUES IN LE BEIRUT POETRY BY JOSEPH HARB BASED ON NORMAN FAIRCLOUGH’S PERSPECTIVE - Saputra Husein Siregar; Ifi Erwhintiana (Arabic Language and Letters Department, 2020)
political polemic and crisis in Beirut has been marked by various actions. The emergence of public aspirations led to tragedy. The occurring of bomb incident as a result of building burning that contained 2,750 tons of Ammonium Nitrate. It can be concrete evidence that freedom in Beirut is at stake. This tragedy caused 100 victims were died and thousands people were injured. This phenomenon made many society from aroun the world contribute to express Beirut’s freedom including Josep Harb through his poetry entitle “li Beirut”. This study aims to describe nationalism form in li Beirut poetry based on Norman Fairclough’s theory, and show its impact on natinalism’s reader as literary connoisseurs. This study is a qualitative descriptive that came from li Beirut poetry by Joseph Harb and supported by related literatures. Data collection are coming from reading and taking notes techniques. Analysis techniques are based on Miles and Huberman model that contained data reduction, data display, and conclusion drawing. The results showed that portrait of nationalism in li Beirut poetry are expressions of love and praising for Beirut, also compassions and hopes for Beirut. The impact that has an effect on readers' nationalism is an attitude of prioritizing unity and brotherhood, as well as an optimistic attitude to improve the nation.